Prevalence and direct costs of potentially inappropriate prescriptions in France: a population-based study. (19th May 2022) - Roux, Barbara; Bezin, Julien; Morival, Camille; Noize, Pernelle; Laroche, Marie-Laure
ABSTRACT: Background: Potentially inappropriate prescriptions (PIPs) in the older population remain a growing public health concern due to the many associated adverse events increasing healthcare service use and health costs. This study aimed to assess the prevalence and direct costs of PIPs in older adults aged ≥65 years in France. Methods: A population-based cross-sectional study was conducted in 2017 using a representative sample of the French national healthcare reimbursement system database. PIPs were defined using the French REMEDI[e]S tool. Overall reimbursed direct costs and by PIP category were extrapolated to the French older population. Results: The overall PIP prevalence was estimated at 56.7% (95% CI: 56.4–57.0). Medications with an unfavorable benefit/risk ratio had the highest prevalence (34.0%, 95% CI: 33.7–34.3). Direct costs associated with PIPs represented 6.3% of the total reimbursed medication costs in 2017 (€507 million). Drug duplications were the main contributors to these costs (39.2% of the total reimbursed PIP costs, €199 million) and among all PIPs, proton pump inhibitors (>8 weeks) were the most expensive PIPs (€152 million). Conclusions: PIP prevalence is still high among French older adults, with substantial direct costs. Large-scale interventions targeting the most prevalent and/or costly PIPs are needed to reduce their clinical and economic impacts.